1983
DOI: 10.1007/bf02332125
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of MP26 in lens junctional membranes: Analysis with proteases and antibodies

Abstract: The major membrane protein of the bovine lens fiber cell is a 26-kilodalton (kD) protein (MP26), which appears to be a component of the extensive junctional specializations found in these cells. To examine the arrangement of MP26 within the junctional membranes, various proteases were incubated with fiber cell membranes that had been isolated with or without urea and/or detergents. These membranes were analyzed with electron microscopy and SDS-PAGE to determine whether the junctional specializations or the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
(49 reference statements)
4
26
0
Order By: Relevance
“…The limited cleavage of MP26 observed here after incubation of membranes with chymotrypsin, trypsin, or V8 protease is consistent with previous reports (27,28). In each case, there is a total loss of 4-5 kDa primarily from the carboxyl terminus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The limited cleavage of MP26 observed here after incubation of membranes with chymotrypsin, trypsin, or V8 protease is consistent with previous reports (27,28). In each case, there is a total loss of 4-5 kDa primarily from the carboxyl terminus.…”
Section: Discussionsupporting
confidence: 92%
“…Several minor bands are always present in these preparations, and some of these are more abundant in membranes prepared from the nuclear region of the lens. One minor band that migrates at a position of 19-20 kDa is consistently present in these preparations and those of others (18 kDa) (10,23,(27)(28)(29)(30). When electrophoresis was performed using gradient gels, these proteins migrated at 28-29 kDa and at 19-22 kDa, respectively.…”
Section: Resultssupporting
confidence: 63%
“…This conclusion is consistent with a number of other studies whch suggested that proteases remove a C-terminal piece with M , = 4000 -5000 from the cytoplasmic side of the lens membrane [40,41]. A less prominent intermediate at M,, app = 25500 (lanes 2, 3) was also present as previously observed [40]. The M,, app = 18000 protein was not as susceptible to chymotrypsin cleavage and did not appear to be degraded as thoroughly in the reaction time course.…”
Section: Properties Of Protein Kinase C Preparationssupporting
confidence: 93%
“…The kinetics of these changes and the similar staining intensities suggested that the M,, app = 22000 protein was a cleavage product of MP26. This conclusion is consistent with a number of other studies whch suggested that proteases remove a C-terminal piece with M , = 4000 -5000 from the cytoplasmic side of the lens membrane [40,41]. A less prominent intermediate at M,, app = 25500 (lanes 2, 3) was also present as previously observed [40].…”
Section: Properties Of Protein Kinase C Preparationssupporting
confidence: 92%
“…3B). Inspection of this figure indicates some 32P is also associated with the 24-kDa componcnt that is derived from the chymotryptic cleavage of some larger lens membrane component [24]. Fig.…”
Section: Resultsmentioning
confidence: 96%